Healthcare System Responsiveness in Covid-19: An Experience from Capital City of I.R of Iran - Ameneh Setareh Forouzan; Arash Mirabzadeh; Katayoun Falahat; Zahra Banazadeh; Monir Baradaran Eftekhari (International Journal of Preventive Medicine, 2023)
Background: As a public health emergency, coronavirus disease 2019 (Covid-19) is a threat to our future; therefore, appropriate health system responsiveness (HSR), as an important criterion, is of crucial importance. This study aimed to evaluate the different dimensions of responsiveness of healthcare centers, both public and private, providing COVID-19 services in Tehran. Methods: Following a cross-sectional design, this study was conducted in Tehran (the capital city of I.R. Iran) from May to November 2020. Data were collected using the World Health Organization (WHO) questionnaire on responsiveness. Two hundred questionnaires were filled out through face-to-face or phone call interviews in two public and private hospitals (100 in each) providing Covid-19 services. Participants were selected using the convenience sampling technique among all those who received Covid-19 services during the past six months in the city of Tehran. Results: The mean age of participants was 45.9 ± 15.9 and 51.5% were female. On an average, 52.6% of the respondents evaluated at least one dimension of responsiveness as appropriate and/or strongly appropriate. Communication obtained the highest score (58.2%), followed by confidentiality (56.5%), dignity (56%), and prompt attention (52%). Meanwhile, autonomy and choice were evaluated as poor (moderate, weak, and strongly weak) by 63.5 and 52.5% of respondents. There was no significant association between the type of healthcare center (i.e., public or private) and responsiveness (p-value = 0.896). However, there was a significant difference between gender (p-value = 0.036) and education level (p-value = 0.014) with responsiveness. According to the respondents, prompt attention and choice were the most and least important dimensions, respectively. Conclusions: Evaluation of HSR in the era of COVID-19 not only provides a tool for qualitative assessment of services but also plays an important role in providing feedback to policymakers to adopt effective policies.